A 93.36 dB, 161 MHz CMOS Operational Transconductance Amplifier (OTA) for a 16 Bit Pipeline Analog-to-Digital Converter (ADC) - Nordiana Mukahar; Siti Hawa Ruslan (Institute of Advanced Engineering and Science, 2012)
A gain modified CMOS Operational Transconductance Amplifier (OTA) for a 16 bit pipeline Analog-to-Digital Converter (ADC) is presented. The circuit is designed to be used for a high resolution and low sampling rate ADC. Gain boosting technique is implemented in the design to achieve high DC gain and settling time as required. Post layout simulations for a 5 pF load capacitance shows that OTA achieves a gain bandwidth of 161 MHz at a phase margin 93.14o with 93.27 dB DC gain. The settling time for an OTA is 163 ns for 0.1 % accuracy to achieve final value and consume power about 4.88 mW from 5 V power supply.Keywords: ADC; common mode feedback; CMOS Operational Amplifier; fully differential folded cascadeDOI:http://dx.doi.org/10.11591/ijece.v2i1.121